Switching on electricity demand response: Evidence for German households - Manuel Frondel; Gerhard Kussel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Empirical evidence on households' awareness of electricity prices and potentially divergent demand responses to price changes conditional on price knowledge is scant. Using panel data originating from Germany's Residential Energy Consumption Survey (GRECS), we fill this void by employing an instrumental-variable (IV) approach to cope with the endogeneity of the consumers' tariff choice. By additionally exploiting information on the households' knowledge about power prices, we combine the IV approach with an Endogenous Switching Regression Model to estimate price elasticities for two groups of households, finding that only those households that are informed about prices are sensitive to price changes, whereas the electricity demand of uninformed households is entirely price-inelastic. Based on these results, to curb the electricity consumption of the household sector and its environmental impact, we suggest implementing low-cost information measures on a large scale, such as improving the transparency of tariffs, thereby increasing the saliency of prices. – – Empirische Evidenz zum Preisbewusstsein und zur Nachfragereaktion auf Preisveränderungen ist für den Stromverbrauch privater Haushalte bislang kaum vorhanden. Wir benutzen die Daten des German Residential Energy Consumption Survey (GRECS), um diese Lücke zu schließen, und verfolgen einen Instrumentvariablenansatz, mit dem wir der Endogenität der Tarifwahl der Verbraucher Rechnung tragen. Indem wir zusätzlich Informationen über die Preiskenntnisse der Haushalte ausnutzen, können wir den IV-Ansatz mit einem Endogenous Switching Regression Model kombinieren und finden heraus, dass nur Haushalte mit Preiskenntnissen auf Strompreisänderungen reagieren, wohingegen die Nachfrage von Haushalten ohne rudimentäre Preiskenntnisse völlig inelastisch ist. Auf Basis dieser Ergebnisse schlagen wir vor, die Transparenz von Stromtarifen zu verbessern, um so die Preiskenntnisse der Verbraucher zu erhöhen.
Keywords: Q41; D12; 330; price elasticity; switching regression model; information